Enhancing suicide risk assessment: a novel visual metaphor learning tool. (December 2016) - Alyami, Mohsen; Alyami, Hussain; Sundram, Frederick; Cheung, Gary; Haarhoff, Beverly A; Lyndon, Mataroria P; Hill, Andrew G
Objective: Suicide risk assessment is variably taught and learnt by health professionals. The literature indicates that training programs of this fundamental competency need to be enhanced. To facilitate teaching and learning of this core clinical skill, we propose a novel visual metaphor in order to conceptualize suicide risk factors. The design of the proposed visual metaphor was informed by the Cognitive Load Theory to enhance deep learning of the various suicide risk factors. Conclusion: The visual metaphor depicting suicide risk factors can potentially improve memory and recall. It activates prior knowledge and is based on educational theory informed design principles.